Preferences for private health insurance in China: A discrete choice experiment - Chen, Nuo; Bai, Jing; Nicholas, Stephen; Maitland, Elizabeth; Tan, Jialong; Wang, Jian (Frontiers in Public Health, 2022)
Introduction: There is limited evidence on the sustainability and optimal design of China’s private health insurance market, especially from the demand-side. With the increasing medical cost burden on both patients and the social security system, policy makers need data on potential clients’ demand for private health insurance. Methods: A discrete choice experiment was conducted to explore potential clients’ preferences for a type of government-involved private supplementary health insurance, Huimin Insurance, in China. A mixed logit model was used to evaluated respondents’ preferences for six attributes. Willingness to pay, subgroup analysis and interaction effects were estimated based on the initial model. Results: Among the 947 participants, 883 (93.2%) were aged 18 to 59 years and 578 (61.0%) were female. Participants had a strong preference for government involvement, extensive benefit packages, high reimbursement ratio and compensation for pre-existing conditions. With respect to the attribute of deductible, participants were indifferent between the level of CNY15,000 and CNY18,000 but had strong and significant preference for the level of CNY15,000 than CNY20,000. The premium was significantly correlated with a decline in the utility of PHI. Conclusions: All attributes had a significant impact on respondents’ preference for Huimin Insurance’s private insurance. Providing a reference point for the development of private health insurance in China, our results inform the optimal design of PHI, especially Huimin Insurance’s products.